Perception of Supervisor Taking Medicine about the Side Effect of Tuberculosis Medication for Patients - Suprajitno Suprajitno; Imam Sunarno; Oky Aditya Ardiansah (STIKes Patria Husada Blitar, 2018)
DOTS strategy is a short-term treatment guide with direct supervision by supervisor taking medicine for tuberculosis patients. Supervisors should know, understand, and be able to distinguish between mild and severe side effects of anti-tuberculosis drugs. The failure of Tb treatment depends on supervisor taking medicine. Currently, never been known the perception of supervisor taking medicine about tuberculosis medication side effect. The purpose of the study to know the perception of the supervisor taking medicine about side effects for clients Tb treatment program in Blitar City. The research design used a descriptive. These result studies show the perception supervisor taking medicine about the side effects as much as 54.5% is the right category and as much as 45.5% is the wrong category. The right category perception may be the supervisor taking medicine ever receive information of tuberculosis medication side effect at the public health center while take a drug. Recommendations for health workers are providing appropriate information to the supervisor taking medicine can be improved with technique counseling and training so that improve knowledge and expertise in the management of medication side effects.